1978
DOI: 10.1159/000148993
|View full text |Cite
|
Sign up to set email alerts
|

An Insect Cell Line Persistently Infected with a Baculovirus-Like Particle

Abstract: A persistent infection by a baculovirus-like particle was found in the established lepidopteran (Heliothis zea) cell line, IMC-HZ-1. The virus caused CPE in less than 1% of the IMC-HZ-1 cells, as measured by phase-contrast and electron microscopy. Transmission tests showed that four lepidopteran cell lines were susceptible to the persistent virus (designated as IMC-HZ-1-NOV). In inoculated TN-368 cell cultures, 90–100% infection was achieved. The ultrastructure and development of IMC-HZ-1-NOV in cell cultures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 7 publications
1
37
0
Order By: Relevance
“…It has an enveloped rod-shaped virion and replicates in the nucleus of infected midgut and fat body cells (Huger 1966, Payne 1974, Payne et al 1977. Heliothis zea nudivirus 1 (HzNV-1), formerly known as Hz-1 virus or the non-occluded baculovirus Hz-1, was originally described as a persistent viral infection in the IMC-Hz-1 cell line isolated from the adult ovarian tissues of the corn earworm Heliothis zea (Granados et al 1978). It can also persistently infect several other lepidopterous cell lines, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It has an enveloped rod-shaped virion and replicates in the nucleus of infected midgut and fat body cells (Huger 1966, Payne 1974, Payne et al 1977. Heliothis zea nudivirus 1 (HzNV-1), formerly known as Hz-1 virus or the non-occluded baculovirus Hz-1, was originally described as a persistent viral infection in the IMC-Hz-1 cell line isolated from the adult ovarian tissues of the corn earworm Heliothis zea (Granados et al 1978). It can also persistently infect several other lepidopterous cell lines, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The baculovirus HZ-1, persistent in IMC-HZ-1 cells, can productively infect TN-368 cells (Granados et aL, 1978) and can establish a persistent infection in TN-368 cells, as demonstrated by infectious centre assays and the detection of virus DNA sequences in TN-P cell nuclei. Persistent viral infections have been linked to temperature-sensitive mutations (Preble & Youngner, 1975) and to DI particles (Huang & Baltimore, 1970).…”
Section: Discussionmentioning
confidence: 99%
“…Granados et al (1978) observed virus particles in the nuclei of approximately 1 ~o of the cells and reported replication of HZ-1 virus in TN-368 cells. Kelly et al (1981) reported virus induction in IMC-HZ-1 cells following superinfection with other baculoviruses as well as u.v.-inactivated virus.…”
Section: Introductionmentioning
confidence: 97%
“…The Hz-1 virus was discovered in a persistently infected Heliothis zea cell culture, IMC-Hz-1 (Granados et al, 1978). Its host range in vitro includes Trichoplusia ni (TN-368), Spodoptera frugiperda (IPLB SF-212), Heliothis zea (IPLB-1075), Mamestra brassicae and Porthetria dispar (IPLB-65Z) (Granados et al, 1978;Ralston et al, 1981;Langridge, 1981;Kelly et al, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Its host range in vitro includes Trichoplusia ni (TN-368), Spodoptera frugiperda (IPLB SF-212), Heliothis zea (IPLB-1075), Mamestra brassicae and Porthetria dispar (IPLB-65Z) (Granados et al, 1978;Ralston et al, 1981;Langridge, 1981;Kelly et al, 1981). Persistent infections have been obtained in the T. ni and S. frugiperda cell lines (Burand et al, 1983b;Ralston et al, 1981).…”
Section: Introductionmentioning
confidence: 99%